Acquisition of an agricultural property by way of acquisitive prescription after amendment to the Civil Code and the Act on the shaping of the agricultural system - Michałowski, Rafał (Przegląd Prawa Rolnego, 2023)
The article concerns the effects of the repeal of Article 172 paragraph 3 of the Civil Code, which provided that only an individual farmer could acquire agricultural real estate by way of acquisitive prescription. The aim of the deliberations is to determine whether, following the repeal of this provision, any entity established under civil law may acquire agricultural real estate by way of acquisitive prescription, or whether acquisition of such real estate in this manner falls within the scope of Article 2a of the Act of 11 April 2003 on the shaping of the agricultural system. In conclusion, the author states that Article 2a of the said Act applies to the acquisition of agricultural real estate by way of acquisitive prescription. Therefore, in principle, agricultural real estate by way of acquisitive prescription may be acquired by an individual farmer. There are also possible some exceptions to this rule as indicated in Article 2a, paragraph 3 of the Act. Doubts, however, arise with regard to the application to acquisitive prescription of agricultural real estate.